1993
DOI: 10.1038/bjc.1993.434
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic radiosensitivity and prediction of patient response to radiotherapy for carcinoma of the cervix

Abstract: Summary The intrinsic radiosensitivity of cervical carcinoma has been measured using a soft agar clonogenic assay. All patients received radical radiotherapy alone with a minimum of 2 years post-treatment follow-up. Only women with stage I, II and III disease were included in the analysis. Values for cell surviving fraction at 2 Gy (SF2) were obtained for 88 tumours with an assay success rate of 73%. The 53 patients alive and well at the time of analysis had tumours with a mean SF2 that was significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
91
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 19 publications
5
91
1
1
Order By: Relevance
“…The success rate for measuring tumour cell radiosensitivity was 68%. Furthermore, the plating efficiency and the overall SF 2 values measured in this study fell within the same range as in similar studies on in vitro radiosensitivity (Brock et al, 1989;West et al, 1989West et al, , 1993Girinski et al, 1994;KocagĹĄncŸ et al, 1994;West, 1995).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The success rate for measuring tumour cell radiosensitivity was 68%. Furthermore, the plating efficiency and the overall SF 2 values measured in this study fell within the same range as in similar studies on in vitro radiosensitivity (Brock et al, 1989;West et al, 1989West et al, , 1993Girinski et al, 1994;KocagĹĄncŸ et al, 1994;West, 1995).…”
Section: Discussionsupporting
confidence: 70%
“…To judge the representativeness of these findings, it is of interest to compare our assay with reports in the literature. The assay used in the current study was similar to the often used modified CourtenayÐMills soft agar clonogenic assay (West et al, 1989(West et al, , 1993, except for the addition of an immunocytochemical analysis for staining colonies from soft agar (StausbÂżl-GrÂżn et al, 1995). The 73% overall success rate in this study is consistent with the overall success rate in previous studies on cellular in vitro radiosensitivity of different tumour types using either CAM assays or soft agar clonogenic assays (Brock et al, 1990;Girinski and Fertil, 1993;KocagĹĄncŸ et al, 1994;West, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This 'intrinsic' radiosensitivity differs largely between tumour types and is at least partly due to the different sensitivity of the respective tumour cells Deacon et al, 1984;Fertil and Malaise, 1985). It was further shown that within one type of tumours, the outcome of the individual patients after radiotherapy was reflected by the in vitro radiosensitivity (SF2) of their tumour cells (West et al, 1993(West et al, , 1995Stausbol-Gron and Overgaard, 1999;BjĂśrk-Eriksson et al, 2000).…”
mentioning
confidence: 99%
“…Furthermore, there is no obvious relationship between the level (XRCC5, XRCC6 and XRCC7) or activity (XRCC7) of DSB repair proteins in human tumour cell lines exhibiting a range of radioresistance (Allalunis-Turner et al, 1995) that impacts on patient radioresponsiveness (West et al, 1993).…”
mentioning
confidence: 99%